Optimization of a rotary desiccant wheel for enthalpy recovery of air-conditioning in a humid hospitality environment. Issue 10 (October 2022) - Tsai, Hung-Yi; Wu, Chung-Tai
Abstract: Excessive condensation on cooling coils can be costly energy-wise due to humid process air streams. An innovative desiccant cooling system is introduced into an existing hotel in Taoyuan, Taiwan, where the ambient is humid year-round. Rejected heat from the existing cooling system is used as the energy source to heat the regeneration airstream for dehumidification of the process airstream via a rotary desiccant wheel. The paper develops and validates a numerical model for the heat and mass (moisture) transfer of the rotary desiccant wheel. The validated numerical model is used to simulate the expected performance of the rotary wheel under various conditions and operating strategies. The desiccant wheel's performance includes the steady-state moisture removal capacity (MRC) and the transient response time to reach steady-state. The examined factors include the ambient temperature and humidity, air flow rate, rotational speed of the wheel, wheel-split, and regeneration airstream temperature. From the simulation results, the paper offers the optimized control strategies for the operation of the rotary desiccant wheel system in the hotel. Abstract : Desiccant wheel; Enthalpy recovery; Moisture removal capacity (MRC).